2011
DOI: 10.1182/blood.v118.21.4729.4729
|View full text |Cite
|
Sign up to set email alerts
|

Volume, Conductivity and Scatter Properties of Leukocytes (VCS Technology) in Detecting Sepsis in Critically Ill Adult Patients

Abstract: 4729 Sepsis and its sequelae remain leading causes of death in critically ill patients. Early identification and subsequently prompt treatment of sepsis can have a major impact on the outcome of septic patients. White Blood Cell (WBC) count, neutrophils count or percentage and percentage of band and immature neutrophils have been included in the diagnostic criteria of sepsis d. Previous studies have shown that morphological changes of leukocytes during sepsis can be quantified using Volume, Cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…To the extent that earlier detection of sepsis leads to earlier treatment, these findings have implications for reducing sepsis mortality. [5][6][7] Consistent with the results of recent human studies, [14][15][16][17][18][19][20][21] and the established function of neutrophils as first responders during the innate immune response to invading organisms, both MNV and NDW were reasonably sensitive and specific for the detection of sepsis (e-Table 5). Based on previous studies demonstrating that changes in neutrophil volume and cell activation markers (CD64) can detect sepsis in hospitalized pediatric patients, 14,17,18,32 we originally expected that neutrophil volume changes would be superior for the detection of sepsis in the ED population.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…To the extent that earlier detection of sepsis leads to earlier treatment, these findings have implications for reducing sepsis mortality. [5][6][7] Consistent with the results of recent human studies, [14][15][16][17][18][19][20][21] and the established function of neutrophils as first responders during the innate immune response to invading organisms, both MNV and NDW were reasonably sensitive and specific for the detection of sepsis (e-Table 5). Based on previous studies demonstrating that changes in neutrophil volume and cell activation markers (CD64) can detect sepsis in hospitalized pediatric patients, 14,17,18,32 we originally expected that neutrophil volume changes would be superior for the detection of sepsis in the ED population.…”
Section: Discussionsupporting
confidence: 82%
“…Volumetric increases are an early manifestation of immune cell responses to severe infections and as such have shown potential as sepsis biomarkers in humans. [14][15][16][17][18][19][20][21] We show that volumetric changes of circulating immune cells, particularly increased MDW, correspond with previously established criteria for sepsis 24 in a large patient population in the ED. MDW distinguished sepsis from SIRS, and the magnitude of MDW elevation correlated with infection severity and organ dysfunction, ranging from normal MDW in those with limited infections, and increasing incrementally with sepsis severity.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In addition, lymphocytes are also an important cellular component of immune response. Volume increases are an early manifestation that these immune cells respond to severe infections and as such have been shown to serve as potential human biomarkers for latent sepsis [8][9][10][11][12]. Our results show changes in the volume of circulating immune cells, especially the increased mean neutrophil volume (MNV), mean monocyte volume (MMV), mean lymphocyte volume (MLV), and monocyte distribution width (MDW).…”
Section: Discussionmentioning
confidence: 71%
“…In addition to detecting routine blood cell parameters, it can also provide quantitative WBC volume, conductivity, and light scatter to reflect the morphological changes of them. Recent studies have shown that the increase in the volume of rudimentary immune cells reflected in the VCS parameter may help detect sepsis [8][9][10][11][12]. However, the application of VCS parameters in sepsis for patients with cirrhosis was less studied.…”
Section: Introductionmentioning
confidence: 99%